2017
DOI: 10.1016/j.jmmm.2016.11.081
|View full text |Cite
|
Sign up to set email alerts
|

Collective coordinate models of domain wall motion in perpendicularly magnetized systems under the spin hall effect and longitudinal fields

Abstract: -Recent studies on heterostructures of ultrathin ferromagnets sandwiched between a heavy metal layer and an oxide have highlighted the importance of spin-orbit coupling (SOC) and broken inversion symmetry in domain wall (DW) motion. Specifically, chiral DWs are stabilized in these systems due to the Dzyaloshinskii-Moriya interaction (DMI). SOC can also lead to enhanced current induced DW motion, with the spin Hall effect (SHE) suggested as the dominant mechanism for this observation. The efficiency o f SHE dri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…Furthermore, considering experiments of fast current-driven DW motion (Ryu et al, 2012), Boulle et al (2013) proposed to include DW tilting as an additional time-dependent variable χ(t) (defined as the angle of the DW normal plane with respect to the positive x-axis), which led to the development of the q − Φ − χ model. Very recently the 1D model was extended to implement all four collective coordinates, namely q − Φ − ∆ − χ, with the aim of improving the agreement with experimental observations and micromagnetic simulations when large in-plane fields are applied (Nasseri et al, 2017). The same authors later showed that the simple two coordinate q − Φ model can grant higher accuracy when combined with an ansatz (which links collective coordinates to magnetization components) that takes into account magnetization canting within the domains under an in-plane field (Nasseri et al, 2018).…”
Section: B Theory and Modelsmentioning
confidence: 99%
“…Furthermore, considering experiments of fast current-driven DW motion (Ryu et al, 2012), Boulle et al (2013) proposed to include DW tilting as an additional time-dependent variable χ(t) (defined as the angle of the DW normal plane with respect to the positive x-axis), which led to the development of the q − Φ − χ model. Very recently the 1D model was extended to implement all four collective coordinates, namely q − Φ − ∆ − χ, with the aim of improving the agreement with experimental observations and micromagnetic simulations when large in-plane fields are applied (Nasseri et al, 2017). The same authors later showed that the simple two coordinate q − Φ model can grant higher accuracy when combined with an ansatz (which links collective coordinates to magnetization components) that takes into account magnetization canting within the domains under an in-plane field (Nasseri et al, 2018).…”
Section: B Theory and Modelsmentioning
confidence: 99%
“…can be proposed with R ≡ η[(x − q) cos χ + y sin χ]/∆. By integrating the resulting dynamical equations over infinite strip length and finite width, the so-called "q − ϕ − χ" [40] or "q − ϕ − χ − ∆" [51,52] models, emerge. However they are too complicated to provide clear physical pictures in analyzing chiral wall dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…For ideal narrow-strip shaped heterostructures when considering the DMI-induced wall tiling χ [28] and canting θ ∞ [37] in domains from in-plane fields, a more complicated wall ansatz tan ϑ 2 = e R + tan(θ ∞ /2) 1 + e R tan(θ ∞ /2) , φ = ϕ(t) (10) can be proposed with R ≡ η[(x − q) cos χ + y sin χ]/∆. By integrating the resulting dynamical equations over strip surface in xy−plane, alternative Lagrangian-based collective coordinate models, such as the "q − ϕ − χ" [28] or "q − ϕ − χ − ∆" [38,39] models, emerge. However they are too complicated to provide clear criteria in constructing operable procedures and explaining experimental data.…”
Section: Discussionmentioning
confidence: 99%